THE POLITICS OF RELIGION THE INVENTION OF “AGAMA” IN INDONESIA - Sita Hidayah (Jurnal Kawistara, 2012)
“Agama” (English: Religion) is a heavily loaded word in Indonesia imbued with a simplistic view that the discourse of “agama” is especially about morality but which is also politically motivated by power interests. The simplicity of the argument is not that it is incorrect, but the valid questions here are: “what the meaning of “agama” isas informed by ethnographies of adat communities, historical archives, media reports, and Indonesian state policies?”This paper examines the ‘condition of possibility’ of the emergence of the discourse of “agama” in Indonesia. Foucault’s theoretical framework is used to investigate the invention of “agama” in Indonesia.Here I limit the discussion to the historical and sociological beliefs and practices that make “agama” possible and focus on “agama” as an operational category in Indonesian politics.This paper links the discourse on “agama” with the discussion of citizenship. Signicant inuence of the discourse of “agama” in the Indonesian systems of government, I argue, has become the most powerful force informing the concept of citizenship in Indonesia. The production of state’s denition of the term “agama” was a rupture marking the construction of a new ‘eld of control’ in the way in which it creates, registers, categorizes, and controls Indonesians’ citizenship; thus citizenship is reinforced or subverted by this specic meaning of “agama”.The formalization of “agama” and regularitiesof the formalized “agama” has consistently been appropriated to legitimate the adoption of every so often violent measures targeting religious minorities in Indonesia. This paper will also highlight the relationship between the discourse of “agama” and the political exclusion of religious minorities in Indonesia